The pact of veridiction in the series Chernobyl. The truth and the historical lie from the film - Blanco Pérez, Manuel (2022)
On 26 April 1986, one of the most important events in the history of nuclear energy took place: the Chernobyl accident. This historic event marked the decline of the Soviet Union, an environmental agenda and new geopolitics of the world. It has been portrayed in literature, film, photo-reportage and documentary, among others. This paper seeks to analyse and contrast the HBO series Chernobyl (2019) and Svetalna Alexievich's Voices from Chernobyl (1997), specifically the relationship between reality and literary and filmic reconstruction. For this purpose, we use a descriptive-argumentative logic and a visual analysis with a mixed methodology. The analysis reveals a conflictive relationship between the two works, since the testimonies recorded in the book are easily recognisable in the series, although the latter has never specified that they are based on the book. Among the conclusions, the narrative structure carrying ideology (which seeks to strengthen a collective imaginary over the commonly accepted biases about the Soviet Union and its model of socialism), carried out with remarkable art direction, stands out. Finally, the series comes at a time of widespread debate in civil society about the use of nuclear energy, just as the end of the current model of fossil fuel-based energy generation for society and heavy industry approaches.